DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE ON THE BASIS OF STEM EDUCATIONAL TECHNOLOGY: HISTORY AND FUTURE - Ahmadjonova, Odina Anvarjon qizi (Innovative Development in Educational Activities, 2023)
The purpose of this study is to investigate one of the urgent issues in the field of education: the features of developing students’ communicative competence through STEM educational technology as well as this article reveals the history and future of teaching English in relation to STEM.